Development of Deterministic Networking Techniques for Industrial Manufacturing - Wang Shuo; Wang Jiasen; Cai Lei; Huang Tao; Lu Hua; Liu Yunjie (中国工程科学, 2021)
Deterministic networking for industrial manufacturing is a frontier technology with both theoretical innovativeness and technical practicability; it is significant for promoting technological innovations of the new-generation industrial Internet and for promoting the integrated development of industrial manufacturing and high-quality network, thereby providing opportunities for occupying the commanding height of network technology and seizing new economic growth points. This study investigates the development requirements for deterministic networking for industrial manufacturing from the aspects of manufacturing and communication enterprises, summarizes the development status and trends of the technology in detail, and further addresses development challenges. We classify the development stages of the technology into pilot demonstration, large-scale replication, and spontaneous innovation. Research reveals that the “deterministic network + industrial manufacturing” development in China needs to focus on the following aspects: establishing industry alliances to improve the industrial ecology, maximizing the existing public networks, carefully selecting industry development paths, increasing resource guarantee for application innovation, strengthening research on basic theories and key technologies, and training personnel through collaboration among industry, universities, and research institutes.